Is Riemann here?

Calculus Level 3

0 x 3 e x 1 d x = ? \int_0^\infty \frac{x^3}{e^x-1}dx=\ ?


The answer is 6.4939.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Note that

ζ ( s ) = 1 Γ ( s ) 0 x s 1 e x 1 d x where ζ ( ) denotes the Riemann zeta function 0 x 3 e x 1 d x = ζ ( 4 ) Γ ( 4 ) and Γ ( ) denotes the gamma function. = π 4 90 ( 4 1 ) ! = π 4 15 6.49 \begin{aligned} \zeta(s) & = \frac 1{\Gamma(s)} \int_0^\infty \frac {x^{s-1}}{e^x - 1} dx & \small \blue{\text{where } \zeta (\cdot) \text{ denotes the Riemann zeta function}} \\ \implies \int_0^\infty \frac {x^3}{e^x-1} dx & = \blue{\zeta (4)} \red{\Gamma (4)} & \small \blue{\text{and }\Gamma (\cdot) \text{ denotes the gamma function.}} \\ & = \blue{\frac {\pi^4}{90}} \cdot \red {(4-1)!} \\ & = \frac {\pi^4}{15} \approx \boxed{6.49} \end{aligned}


References:

I = 0 x 3 e x 1 d x I=\int_0^∞\frac{x^3}{e^x-1} dx = 0 x 3 ( n = 1 e n x d x ) \int_0^∞ x^3( \displaystyle\sum_{n=1}^∞ e^{-nx}dx)

I I = n = 1 0 x 3 e n x d x \displaystyle\sum_{n=1}^∞ \int_{0}^∞ x^3 e^{-nx}dx

let's take n x = u nx=u so n = d u / d x n=du/dx

I I = n = 1 1 n 0 u 3 n 3 e u d u \displaystyle\sum_{n=1}^∞ \frac{1}{n} \int_{0}^∞ \frac {u^3}{n^3} e^{-u} du

I I = n = 1 1 n 4 Γ ( 4 ) \displaystyle\sum_{n=1}^∞ \frac{1}{n^4} Γ(4)

Note Γ ( s ) Γ(s) = 0 x s 1 e x d x \int_{0}^∞ x^{s-1} e^{-x}dx

And Γ ( s ) Γ(s) = ( s 1 ) ! (s-1)!

I = Γ ( 4 ) n = 1 1 n 4 I =Γ(4) \displaystyle\sum_{n=1}^∞ \frac{1}{n^4}

I = 3 ! ζ ( 4 ) I = 3! ζ(4)

I = 6 × π 4 90 I =6×\frac{π^4}{90}

I = π 4 15 I= \boxed{\frac{π^4}{15}}


In general 0 x n e x 1 = n ! ζ ( n + 1 ) \int_{0}^∞ \frac{x^n}{e^x-1} = n!ζ(n+1)

@Dwaipayan Shikari , you can key in as \int_0^\infty 0 \int_0^\infty . Notice that you don't need braces { } for a single character.

Chew-Seong Cheong - 7 months, 1 week ago
Karan Chatrath
Nov 6, 2020

I = 0 x 3 e x 1 d x I = \int_{0}^{\infty} \frac{x^3}{\mathrm{e}^x-1} \ dx

Multiplying numeritor and denominator by e x \mathrm{e}^{-x} gives: I = 0 e x x 3 1 e x d x I = \int_{0}^{\infty} \frac{\mathrm{e}^{-x}x^3}{1 - \mathrm{e}^{-x}} \ dx

Expanding the denominator as an infinite geometric series, gives: I = 0 x 3 ( e x + e 2 x + e 3 x + e 4 x + ) d x I = \int_{0}^{\infty} x^3\left( \mathrm{e}^{-x} + \mathrm{e}^{-2x} + \mathrm{e}^{-3x} + \mathrm{e}^{-4x} + \dots\right) \ dx e x < 1 x > 0 \because \mathrm{e}^{-x}<1 \ \forall \ x>0 I = k = 1 ( 0 x 3 e k x d x ) I = \sum_{k=1}^{\infty} \left( \int_{0}^{\infty}x^3 \mathrm{e}^{-kx} \ dx\right)

Let:

I 2 = 0 x 3 e k x d x I_2 = \int_{0}^{\infty}x^3 \mathrm{e}^{-kx} \ dx Let: k x = z kx = z . This transforms the integral to:

I 2 = 1 k 4 0 z 3 e z d z I_2 = \frac{1}{k^4}\int_{0}^{\infty}z^3 \mathrm{e}^{-z} \ dz I 2 = Γ ( 4 ) k 4 I_2 = \frac{\Gamma(4)}{k^4}

Γ ( 4 ) = 3 ! \because \Gamma(4)=3! I 2 = 6 k 4 \implies I_2 = \frac{6}{k^4}

Using the above result in I I gives:

I = k = 1 ( 0 x 3 e k x d x ) = k = 1 6 k 4 I = \sum_{k=1}^{\infty} \left( \int_{0}^{\infty}x^3 \mathrm{e}^{-kx} \ dx\right) = \sum_{k=1}^{\infty} \frac{6}{k^4}

I = 6 k = 1 1 k 4 I = 6\sum_{k=1}^{\infty} \frac{1}{k^4} I = 6 ζ ( 4 ) I = 6 \zeta(4) I = 6 ( π 4 90 ) I = 6\left(\frac{\pi^4}{90}\right) I = π 4 15 I = \frac{\pi^4}{15}

ζ ( 4 ) = π 4 90 \because \zeta(4) = \frac{\pi^4}{90}

Where ζ ( n ) \zeta(n) denotes the Reimann-Zeta function and Γ ( n ) \Gamma(n) denotes the Gamma function.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...